Role of inhibitor behavior in abnormal growth of Goss grain in grain-oriented silicon steel: experiments and modeling - Feng Fang; Shuaifa Dai; Yuanxiang Zhang; Yang Wang; Guo Yuan; Mingtao Wang; Guodong Wang (Journal of Materials Research and Technology, 2023)
The role of inhibitor behavior in abnormal growth of Goss grains during secondary recrystallization was studied in combination with experimental observation and phase-field model simulation in grain-oriented silicon steel. The frequency advantages of both HE (high energy) and CSL (coincidence site lattice) grain boundaries around Goss grains over the matrix were identified, with frequency advantages of ∼15% and ∼2% respectively. The HE grain boundary was supposed to play a more important role in abnormal grain growth over CSL grain boundary in this study. The boundary character distribution was necessary but not sufficient for the abnormal growth of Goss grains. Appropriate inhibitor behavior was a prerequisite for secondary recrystallization. The initial content and stability of inhibitor played a key role in stabilizing the matrix, which guaranteed beneficial fine grains around Goss grains. While if the inhibitor force rapidly declined, matrix grains might grow obviously, resulting in coarsened grain colonies with Cube, {112}<110>, {111}<112>, {411}<148>and {210}<001> orientation, which further hindered the abnormal growth of Goss grains. The candidate Goss grains with different misorientations competed with each other during secondary recrystallization and the exact Goss grain exhibited an obvious growth advantage. Only with an appropriate pinning force and grain boundary character, perfect secondary recrystallization can be achieved. The present findings can provide guidance to understand and precise control of abnormal grain growth phenomenon.